ANALISIS PENILAIAN KESEHATAN KOPERASI JASA KEUANGAN SYARIAH BERBASIS MASJID (STUDI KASUS KOPERASI JASA KEUANGAN SYARIAHBAITUL MAL TAMWIL AT-TAQWA-MASJID AT-TAQWA KEMANGGISAN JAKARTA) - Hasmayati, Hasmayati (Economic Faculty, Attahiriyah Islamic University, 2016)
The purpose of this study was to analyze the soundness and analyzes the factors that affect the soundness of BMT Syariah Cooperative Financial Services At-Taqwa and to find a formula the right strategy in the development of BMT Syariah Cooperative Financial Services At-Taqwa. This study uses a quantitative descriptive analysis of health assessment and qualitative description on service quality. The research proves that the level of health KJKS BMT At-Taqwa through computation eight aspects (six financial aspects and the two aspects of the non-financial) shows KJKS BMT At-Taqwa at the level reasonably healthy and is influenced by factors of seven financial ratios are on the effects on health of the Cooperative. In addition there is a five-part strategy that can be developed by BMT KJKS At-Taqwa ie services and the addition of customers, financing, dissemination and promotion, health cooperatives, blue print and build a cooperative networking. Keywords: financial health, koperasi